High-Resolution Wavefront-Guided Photorefractive Keratectomy and Accelerated Corneal Crosslinking for Stabilization and Visual Rehabilitation of Keratoconus Eyes - Tamayo GE (Dove Medical Press, 2020)
Gustavo E Tamayo, Claudia Castell, Pilar Vargas, Eduardo Polania, Juliana Tamayo Bogota Laser Ocular Surgery Center, Bogota, ColombiaCorrespondence: Gustavo E Tamayo Tel +1 305 987 0527Email centrogustavotamayo@gmail.comPurpose: To evaluate the visual and refractive outcomes after high-resolution wavefront-guided (HRWG) surface ablation with corneal crosslinking (CXL) in keratoconus eyes.Patients and Methods: In this prospective, interventional case series, 47 eyes of 28 progressive keratoconus patients older than age 18 were enrolled. All patients underwent HRWG photorefractive keratectomy (PRK) with simultaneous accelerated CXL. The study parameters were manifest refraction spherical equivalent (MRSE), keratometric outcomes, uncorrected (UDVA) and corrected distance visual acuity (CDVA) at postoperative 6 and 12 months.Results: There was improvement in mean MRSE from − 2.39± 1.89 D preoperatively to − 0.13 ± 0.68 D at 12 months, with corresponding improvement in UDVA from 0.77 ± 0.35 logMAR to 0.08 ± 0.12 logMAR and CDVA from 0.10 ± 0.11 logMAR to 0.02 ± 0.04 logMAR. Preoperative flat and steep keratometry (K) were 4wct 32.49 ± 1.67 D and 45.94 ± 2.10 D, respectively, and at postoperative 12 months were 41.36 ± 2.08 D and 42.65 ± 2.78 D, respectively. At postoperative 12 months, visual and refractive outcomes were maintained. Comparisons between preoperative and postoperative 12 month timepoints were statistically significant for all parameters.Conclusion: Simultaneous wavefront-guided PRK followed by CXL is a promising treatment for the visual rehabilitation of keratoconus patients.Keywords: keratoconus management, high-resolution wavefront-guided surface ablation with corneal crosslinking, wavefront-guided PRK with CXL